Enhancing Student’s Speaking Ability Through Savi (Somatic, Auditory, Visual and Intellectual) Method at Sma Islam Makassar (A Classroom Action Research) - Riswan Awing; Baso Jabu; Samtidar (Program Studi Magister Pendidikan Bahasa Inggris, Fakultas Bahasa dan Sastra- Universitas Negeri Makassar., 2024)
This research aimed to improve the students’ speaking skill in English lesson by using SAVI Method. This research was conducted by using Classroom Action Research (CAR). The subject of this research was X grade of SMA Islam Makassar 2023 / 2024 academic year which consisted of 17 students. The objective of this research was to improve students’ speaking skill in English Lesson by using SAVI Method at Tenth Grade of SMA Islam Makassar. This research was conducted in two cycles which each consists’ of planning, acting, observing, and reflecting. The data were gathered through quantitative and qualitative data. The result of this research showed that there was increasing of students in speaking skill. The mean of pre-test was 62.41, post-test 1 was 76.64, and post-test 2 was 84,4. It indicated that the scores and the mean in second cycle were better than the first cycle. The percentage of the pre-test who got point >75 up was 17,69%, the post-test of cycle 1 was 70.59%, and the post-test of cycle 2 was 94,12%. It can be concluded that the students’ ability in speaking improved and became well in the first meeting to the next meeting.